“FRUITMOB” Website Design Distribution Optimization In Imported Fruit Supply Chain System - Burhani, M. Abi Yazid; Fitriah, Fana; Indriyanti, Anggita (Universitas Muhammadiyah Yogyakarta, 2024)
Supply chain system is a management activity carried out by all parties such as the companies who related to a supply chain scope. The analysis was carried out at Sinar Buah Giwangan's store. And there was a problem in the distribution process whom was limited information with distributors. This research were analyzed using PIECES method and based on observations at the Sinar Buah Giwangan's store. With PIECES method, there was a serious problem that's hampering the imported fruit supply chain process. It's the stock of fruit at distributors and the distribution itself. This thing has an impact on order information, fruit distribution, and irregular fruit stock. In this research we designed a website called fruitmob. Fruitmob is a website designed to facilitate the fruit import process with a supply chain management system. In designing this website, a platform is available for distributors to provide information on fruit stocks to make it easier for retailers to access information on fruit stocks availability. This website has a feature that can display an ordering system that allows customers to track the whereabouts product they orders and received real-time updates about delivery status. By designing this website, our hope is the supply chain system for distributors and retailers can be fulfilled and resolve the problems in an integrated manner with a system design that facilitates communication to achieve maximum sales & profit optimization. This research produces output in the form of a Business Process Model and Notation (BPMN) design and user interface.